Water-in-oil-in-water multiple emulsions of ibuprofen for paediatrics using african walnut seed oil - Ogundipe, Omotola Deborah; Oladimeji, Francis Abiodun (Journal of Applied Pharmaceutical Research, 2019)
Multiple emulsions (MEs) have been used to prolong drug release from formulations. Hence, this study formulated water-in-oil-in-water (w/o/w) MEs of ibuprofen using African walnut seed oil (AWSO) for paediatrics use. The MEs were prepared by a two-step emulsification method, using Span 80® and Tween 80® as primary and secondary emulsifiers, respectively. The physical properties, drug entrapment efficiency, stability and drug release profile of the MEs were determined. From the study, stable MEs of ibuprofen (100 mg / 5 ml) can be prepared with 25 % w/v Span 80® as the primary emulsifier, and 8, 10 or 12 % w/v Tween 80® as the secondary emulsifier. The optimum ratios of oil to water in the primary emulsion were 1:1 and 3:2, while that of primary emulsion to external aqueous phase were 1:1 and 1:2. The release of ibuprofen from the MEs was ? 35.6 % at 5 hours. The study offers ibuprofen emulsions which may require once daily dosing compared to other available paediatric dosage forms of the drug which require three to four times dosing daily. It also provides information on AWSO as a possible drug carrier in the formulation of w/o/w MEs of ibuprofen for paediatrics.